Tissue-engineered bone for treatment of combat related limb injuries - Vasyliev, R.G.; Oksymets, V.M.; Rodnichenko, A.E.; Zlatska, A.V.; Gubar, O.S.; Gordiienko, I.M.; Zubov, D.O. (Experimental Oncology, 2017)
Aim: Based on our preliminary positive clinical results with use of cultured bone marrow-derived multipotent mesenchymal stem/stromal cells in traumatology, our aim was to develop living three-dimensional tissue-engineered bone equivalent transplantation technology for restoration of critical sized bone defects caused by combat related high energy trauma. Materials and Methods: To fabricate bone equivalent we used devitalized allogeneic bone scaffolds (blocks and chips) seeded with cultured autologous cells: bone marrow-derived multipotent mesenchymal stem/stromal cells in mix with periosteal progenitor cells and endothelial progenitor cells. Quality/identity of cell cultures was assured by donor and cell culture infection screening (immunofluorescence assay, polymerase chain reaction), flow cytometry (cell phenotype), karyotyping (GTG banding), functional assays (colony forming units analysis, multilineage differentiation assay). Bone defect treatment with bone equivalent application was fully completed in 39 combat-injured with 42 defects. New bone formation was assessed by the radiographic examination. Results: Casualties were included in a treatment program an average of 10.1 months after injury, provided the ineffectiveness of conventional surgery methods. All cell type cultures had a normal karyotype and appropriate phenotype, differentiation potential and functional properties, ~30% colony forming units frequency and hadn’t any signs of cell senescence. The fluorescein diacetate/propidium iodide combined staining and histology analysis of graft samples before transplantation showed their regular seeding with viable cells. Pathomorphological analysis of bone equivalent specimens 3–6 months post-op revealed the active remodeling processes and immature bone tissue formation. Bone defect restoration was observed 5–6 months post-op. Conclusion: The developed biotechnology of living three-dimensional tissue-engineered bone equivalent transplantation with overall effectiveness 90.4% allows restoring the bone integrity, forming new bone tissue in a site of bone defect, and significantly reducing the rehabilitation period of a patient.